A Case of Severe Bronchial Asthma Controlled with Tacrolimus. (6th April 2011) - Taniguchi, Hirokazu; Tokui, Kotaro; Iwata, Yasuhiro; Abo, Hitoshi; Izumi, Saburo
Abstract : Background . The control of severe bronchial asthma, such as corticosteroid-resistant asthma, is difficult. It is also possible that immunosuppressive agents would be effective for bronchial asthma. Case Summary . A 55-year-old Japanese female presented with severe bronchial asthma controlled with tacrolimus. She had been diagnosed with bronchial asthma during childhood. Her asthma worsened, and a chest radiograph showed atelectasis of the left lung. Bronchoscopy revealed the left main bronchus to be obstructed with viscous sputum consisting of 82% neutrophils and no eosinophils. The atelectasis did not improve with corticosteroid treatment, but was ameliorated by administration of tacrolimus. Discussion . This patient had severe asthma due to neutrophilic inflammation of the airways. Tacrolimus is effective for treating severe asthma, for example, in corticosteroid-resistant cases.